(untitled) (Research, Society and Development, 2022)
This article aims to describe the challenges faced by the LGBTQIA+ population in a public environment in Belém, Pará. This is an experience report, using an interview (conversation), which has a homosexual as a participant. To speak of homosexuality is to speak of human sexuality, of sexual diversity, rescuing elements to understand meanings and senses of this social construction still confronted and discriminated against by society. It is evident that, in Brazil, there is still little knowledge of the health needs of the homosexual population, knowledge that is essential to foster the development of public policies involving health/education and social/political issues directed at the category. The experience in question highlights the importance attributed to gender identification in the formation of the individual as a social being, highlighting the need for discussions that support the theme in the academic training of health professionals in the construction of a cautious, empathetic, calm, natural and respectful care. It is necessary for professionals in the sector to be closer to public policies and the specific problems of the LGBTQIA+ population in order to qualify the services provided by the various areas.